Strategi Diversifikasi dan Pengembangan Portofolio Bisnis Pada Perusahaan Milik Negara PT. Hutama Karya : Diversification Strategy And Business Portfolio State Ownership Entreprise Pt. Hutama Karya - Ahmad Maulana; Syarief, Rizal; Taryana, Asep (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2024)
This research aims to analyse the business diversification strategy of PT Hutama Karya (Persero) and its subsidiaries, explain their business operations, and explore growth potential. This research tries to identify the company's internal and external environmental factors after business diversification, conduct an analysis of the corporate position and portfolio of business units and subsidiaries, and formulate a new business diversification strategy concept. This research method is descriptive qualitative with the data used in the research including primary data collected through interviews and questionnaires, as well as secondary data such as company financial reports, industry performance reports, and industry attractiveness. PT Hutama Karya's business diversification includes expansion into various business divisions, including Toll Road Business Entity (BUJT), Non-Toll Road Business Entity (Non-BUJT), and the establishment of subsidiaries such as Hutama Karya Infrastruktur (HKI), HAKAAston, HK Realtindo, Hutama Marga Waskita (HAMAWAS), and EPC Energy Singapore Ltd. The main supporting factors for this diversification are the continued economic growth and government support in infrastructure development. The company's internal strengths are the application of technology and adaptation to changes in the construction industry, they also face challenges such as cashflow issues, global economic uncertainty, and changes in political direction. The SWOT analysis shows that the company is in the "Grow and Build" quadrant and needs to pursue aggressive business diversification. The results of the GE Nine Cell Matrix analysis show a diverse position for the company's business units, with some as "Leaders" and others needing to be managed carefully or even divested.The managerial implications of this study are the need for business ecosystem development and business portfolio diversification, technology development across businesses to support competitive advantage, and the creation of new opportunities after the completion of the Trans-Sumatra Toll Road project.